Preemptive Ketorolac is as Effective as Oxycodone Decreasing Plasma Cortisol Levels in Patients Undergoing Spinal Anesthesia - Rizal Zainal; Nugraha Heryadi; Agustina Br Haloho; Erial Bahar (Journal of Anesthesiology and Clinical Research, 2021)
Introduction: Post-surgical pain is a complex problem, if not treated properly it can have multisystem negative effects. Hormone cortisol can be increased in stressful situations. A study on the effectiveness of ketorolac and another opioid on cortisol levels has been shown. However, a study about the effect of oxycodone on cortisol levels and its comparison with Ketorolac has never been done before. This study aimed to compare the effect of preemptive administration of 30 mg ketorolac and 5 mg oxycodone on plasma cortisol levels in patients undergoing spinal anesthesia. Methods: A double-blind randomized clinical trial was carried out between October and December 2020 in the central operating room of dr. Mohammad Hoesin Palembang. Surgical patients according to the inclusion criteria who received spinal anesthesia were randomly given 5 mg oxycodone and 30 mg ketorolac intravenously shortly after spinal anesthesia. Cortisol levels were measured before and after the intervention. Data analysis using SPSS ver. 20 Windows with a 95% confidence interval. Result: In total, 56 subjects were included. 29 samples in the ketorolac group and 27 samples in the oxycodone group. There were no significant differences in age, sex, nutritional status, blood sugar, and VAS score. There was no significant difference in the mean of cortisol levels before the intervention in the ketorolac group 12.9421 + 6.096 m/dL and the oxycodone group 14.033 + 4.315 m/dL (p = 0.446). The mean value of cortisol levels after intervention in the ketorolac group was 12.979 + 6.280 m/dL and oxycodone 15.353 + 11.704 m/dL, there was no significant difference in changes in cortisol before and after intervention in the Ketorolac group (p = 0.692) and Oxycodone (p = 0.552). The comparison level of cortisol changes between the two groups was not significantly different (p = 0.267). Conclusion: There was no difference in the comparison of the effect of preemptive administration of 30 mg IV ketorolac and 5 mg IV oxycodone on plasma cortisol levels in patients undergoing spinal anesthesia.